Política nacional de combate ao bullying: um estudo sobre a implementação das leis antibullying (leis nº 13.185/2015 e 13.663/2018) nas escolas de ensino fundamental de Imperatriz-MA - SOUSA, Deisy Sanglard de (2021)
This dissertation has as its object of study the national policy to combat bullying. Its general objective is to analyze the actions to implement the anti-bullying laws (Laws nº13.185/15 and 13.663/2018) in elementary schools in Imperatriz-MA, from the perspective of teachers and managers. Therefore, we analyzed the National Program to combat bullying and its relationship with public educational policies in accordance with regulatory frameworks such as the Federal Constitution of 1988, the International Convention on the Rights of the Child, the Child and Adolescent Statute and the current Law of Guidelines and Basics of Education. The investigation started from the description of the bullying phenomenon as a kind of school violence, its main manifestations and subjects involved; we analyzed the legal means of coping, in order to know and understand the perception of school agents in the fight against bullying. The methodological perspective adopted was the qualitative approach, with document analysis and semi-structured interviews as data collection instruments. The field research was carried out in two schools, one in the public network and the other in the private school system in Imperatriz-MA. For the analysis of the collected data, we adopted content analysis. The research highlighted bullying as a violent and growing reality in schools and beyond. An attack not simply on the integrity of those involved, but on human dignity in its broadest sense, that of respect for living and living in harmony with diversity. As for the implementation actions to confront and analyze the related legal instruments, we concluded that there was legislative progress and, within the schools, teachers and managers recognize the joint responsibility, the urgency and importance of combating the problem, they act, even if without the necessary technical and scientific training There is still a long way to go, the results express that the “curative” actions outweigh the preventive ones, generally aiming to simply “punish the aggressor”; they are eventually carried out by the school agents themselves, and they still do not have sufficient support from the responsible public entities to enable systematic confrontation. As the final product of the research, we built a digital pedagogical booklet, in clear language, with textual didactic resources, entitled: Bullying, we need to talk about it: prevention and awareness, possible ways of coping.